PERLINDUNGAN HUKUM BAGI PEMBELI TANAH YANG TANAHNYA TELAH DIALIHKAN OLEH PENJUAL KEPADA PIHAK KETIGA (STUDI PUTUSAN NOMOR 635/PDT/G.2013.PN.MDN) - KRISTI DWI SARAH (PREMISE LAW JURNAL, 2017)
PPJB (Buy and Sell Binding Agreement) containing clauses on their rights and obligations. A buyer’s obligation is to pay for the land price, while the seller has to hand over the title over the traded land, i.e., a certificate of the title over the land. However, in the Medan District Court’ Ruling No. 635/Pdt/G. 2013.PN.MDN, This is a normative juridical research with library study or secondary data. This research employs a case study with descriptive analysis. that Article 1320 of the Civil Code is not fulfilled to legalize the agreement. An agreement is considered illegitimate if a fraud constitutes the background for it. The analysis of the Judge’s Ruling also proves that the seller had committed an unlawful act because he has resold the land to another party. What has been decided by the Panel of Judges of Medan District Court i.e. revoking the Buy and Sell Agreement between the seller and the buyer   Keywords: Buy and Sell, Land, Third Party